Actuator Fault Diagnosis Using Probabilistic Ultimate Bounds - Pizzi, Noelia Belén (2016)
This work proposes a fault diagnosis scheme where the occurrence of failures is detected when certain trajectories reach some probabilistic sets, allowing the presence of unbounded disturbances. This is the first result that makes use of probabilistic sets, establishing a first connection between set-based and probabilistic fault diagnosis.